A guidance framework to aid in the selection of nursing and midwifery care process metrics and indicators. Issue 3 (16th April 2019) - Murphy, Fiona; Doody, Owen; Lyons, Rosemary; Brenner, Maria; O'Connor, Laserina; Hunter, Andrew; Devane, Declan; Sezgin, Duygu
Abstract: Aim: To describe the development of a guidance framework to assist nurses and midwives in selecting nursing and midwifery care process metrics and indicators for use in practice. Background: Process metrics are measures of care provision activities by nurses and midwives. Methods: Phase 1 was a rapid review assessment of the literature conducted to identify an initial framework. Six electronic databases were searched with Google Scholar and reference tracking performed. Phase 2 was expert review of the developing framework by nursing and midwifery experts in practice, academia and an international expert in quality care metrics. Results: The literature assessment yielded 28 papers with 59 metric attributes identified. From this, a six‐domain framework was developed. Following expert review, the framework was reduced to four domains: "Process Focused, " "Important, " "Operational" and "Feasible." Conclusions: This is the first framework specifically to guide nurses and midwives in selecting nursing and midwifery process metrics and indicators.